Literasi Digital dengan Penggunaan PHET untuk Remediasi Miskonsepsi Mahasiswa pada Materi Rangkaian Arus Searah - Nur Aida (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
Misconceptions are misunderstandings in connecting a concept with other concepts, between new concepts and concepts that already exist in students' minds, so that a wrong concept is formed and contradicts the concepts of Physicists. The purpose of this research is to find out whether there is an effect of digital literacy with PhET simulations in improving students' concepts about direct current electric circuits. The method in this research is descriptive method. The sample in this study was 22 students in the first semester of the 2022/2023 academic year. Students still experience misconceptions about direct current circuits in using calculation formulas, and the use of digital literacy in the form of PhET simulations has not helped overcome these problems, because as many as 35% of students still have misconceptions about multiple circuits.